Paediatric polyposis syndromes: burden of disease and current concepts. Issue 5 (October 2021) - Phen, Claudia; Rojas, Isabel
Abstract : Purpose of review: Polyposis syndromes are rare but significant entities that often present during childhood and adolescence. Polyposis syndromes should remain high on the differential diagnoses for any child presenting with rectal bleeding, protein-losing enteropathy or intussusception in the setting of multiple polyps in the gastrointestinal tract. There are three primary paediatric polyposis syndromes: Juvenile polyposis syndrome (JPS), Familial adenomatous polyposis (FAP) and Peutz-Jeghers syndrome (PJS). This review will cover recent guidelines for these conditions and advances in genetic testing. Recent findings: The first set of paediatric guidelines were released in 2019 by the European Society for Pediatric Gastroenterology, Hepatology and Nutrition (ESPGHAN) for FAP, JPS and PJS. Even with advances in genetic testing, a significant proportion of patients with polyposis syndromes have no identifiable genetic mutations. Recent research has shown that polyps behave differently in patients with and without disease-causing variants, emphasizing the role of genetic testing in the diagnosis and management of polyposis syndromes. Summary: Polyposis syndromes in the paediatric population are growing due to increased recognition and advances in genetic testing. A timely diagnosis and surveillance of a paediatric polyposis syndrome are pivotal for the management of disease burden and early identification of cancers within the gastrointestinal tract and beyond. Paediatricians, paediatric gastroenterologists, paediatric oncologists and paediatric surgeons should be familiar with the presentation and comorbidities of polyposis syndromes in children and adolescents. Further research into genotype-phenotype correlations is needed to tailor the care for paediatric patients with polyposis syndromes.